2015
DOI: 10.1097/j.pain.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

Who is healthy? Aspects to consider when including healthy volunteers in QST-based studies—a consensus statement by the EUROPAIN and NEUROPAIN consortia

Abstract: Clinical and human experimental pain studies often include so-called "healthy" controls in investigations of sensory abnormalities, using quantitative sensory testing (QST) as an outcome measure. However, the criteria for what is considered "healthy" vary among the different studies and between study centers and investigators, partly explaining the high variability of the results. Therefore, several aspects should be considered during inclusion of healthy volunteers in QST-based trials to have homogenous group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 105 publications
4
53
0
1
Order By: Relevance
“…A recently published consensus paper defines the characteristics of healthy subjects in quantitative sensory testing studies. 11 For the reader to ascertain susceptibility to bias, we suggest in future studies the source of the target population, the sampling frame and methods of recruitment, the place or places and dates of recruitment, study inclusion and exclusion criteria, the numbers recruited to the numbers enrolled, and baseline characteristics of the study sample are reported. In addition to facilitating the assessment of risk of bias, more thorough description of a study sample aids the generalization of results to other populations (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently published consensus paper defines the characteristics of healthy subjects in quantitative sensory testing studies. 11 For the reader to ascertain susceptibility to bias, we suggest in future studies the source of the target population, the sampling frame and methods of recruitment, the place or places and dates of recruitment, study inclusion and exclusion criteria, the numbers recruited to the numbers enrolled, and baseline characteristics of the study sample are reported. In addition to facilitating the assessment of risk of bias, more thorough description of a study sample aids the generalization of results to other populations (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…42 Recommendations for future reliability studies include due consideration of how the results for a sample of participants may be generalized to a population of interest. Gierthmuhlen et al 11 has described important data collection domains for healthy volunteer quantitative sensory testing studies which may be equally pertinent for dynamic measures such as CPM, including but not limited to sociodemographic data, medical history and current health status, pain coping strategies, psychological factors, history of alcohol and drug abuse, smoking and use of recreational drugs, current medication, depression and anxiety scores, the frequency of any pain episodes during the last 3 to 6 months, and self-reported sleep measurements. Consideration should be given to blinding of both the investigator and the participants of CPM studies, standardization of test instructions, and as to how the test environment and exposure to investigators and other study participants may bias performance or results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 Demographic data on healthy subjects and patients suffering from polyneuropathy or peripheral nerve injury for all centers. Details on inclusion and exclusion criteria for entry of the DFNS and IMI Europain and Neuropain database can be found for patients in Maier et al 16 and Demant et al, 4,5 respectively, and for healthy subjects in Gierthmühlen et al 10 …”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Although DNIC seem to be more effective in animals after tissue injury, CPM is often impaired in humans with chronic pain (de Resende et al, 2011; Staud, 2012). Nevertheless, it is important to note that the criteria characterizing normal and deficient CPM using QST vary largely among the different studies (Gierthmühlen et al, 2015). …”
Section: Clinical Relevance Of Pain Modulationmentioning
confidence: 99%